Perancangan Sistem Informasi Penjualan Berbasis Website Menggunakan Framework CodeIgniter - Rafli Erlangga; Arry Avorizano (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Toko Ammar Market is a store that sells basic necessities on Jalan Wailola, Bula City, Maluku. However, in the current data processing system, finding information such as inventory counts, sales figures, and transaction records can be a hassle because it still relies on human processes or manual methods. To overcome this problem, researchers recommend creating a website-based sales information system that can help Ammar Market Stores manage data and facilitate sales transactions in their business. In developing this system, researchers used the CodeIgniter framework and applied the waterfall development method. This designed information system has significant benefits in increasing the efficiency of store operations. By using this information system, the time needed to enter sales data and prepare reports becomes easier, so that store staff can focus more on other more important activities. In addition, the use of this information system also reduces the possibility of human error and provides management with more accurate information for decision-making. With this system, the error rate in data processing by staff can be reduced, and the process of processing employee data becomes smoother and more efficient. In other words, this sales system provides convenience and efficiency in transaction and data management that contributes to better store performance